1990
DOI: 10.1021/es00073a009
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and fluxes of polycyclic aromatic hydrocarbons and polychlorinated biphenyls across the air-water interface of Lake Superior

Abstract: Concentrations of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) were measured in the atmosphere and surface waters of Lake Superior to estimate the direction and magnitude of their fluxes across the air-water interface. Atmospheric PAH concentrations ( [ ] = 3.8 ± 1.7 mg/m3, 13 PAHs) were typical of levels found in continental background air. Atmospheric PCB concentrations (x = 1.2 ng/m3) have remained relatively constant over the Great Lakes during the past 10 years despite low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
199
2
12

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(226 citation statements)
references
References 29 publications
13
199
2
12
Order By: Relevance
“…In addition, a significant contribution of the high molecular weight compounds (HMW), encompassing from benzo-[ghi]fluoranthene (B(ghi)Fla) to coronene (Cor) (log K ow > 5), was also found in the SPM. This qualitative distribution is similar to that observed in other remote lake waters in Europe and USA (Baker and Eisenreich, 1990;Gevao et al, 1998;Vilanova et al, 2001b).…”
Section: Polycyclic Aromatic Hydrocarbons (Pah)supporting
confidence: 89%
“…In addition, a significant contribution of the high molecular weight compounds (HMW), encompassing from benzo-[ghi]fluoranthene (B(ghi)Fla) to coronene (Cor) (log K ow > 5), was also found in the SPM. This qualitative distribution is similar to that observed in other remote lake waters in Europe and USA (Baker and Eisenreich, 1990;Gevao et al, 1998;Vilanova et al, 2001b).…”
Section: Polycyclic Aromatic Hydrocarbons (Pah)supporting
confidence: 89%
“…For that reason, the distribution of atmospheric PAHs between particulate and gas phases is influenced by several factors, such as PAH vapor pressures (function of the temperature), amount of fine particles (surface area for PAH adsorption), ambient temperature, PAH concentration, and affinity of each PAH with the particles of the organic matrix (Baker and Eisenreich, 1990). Reports regarding the seasonal effect on gas-particle equilibrium variations have been found for the winter months, showing a greater concentration of PAHs in the solid phase (Tsapakis and Stephanou, 2005).…”
Section: Characterization Of the Pah Profilementioning
confidence: 99%
“…However, a slope of -1 in plots of Log K, versus Log PLOis rarely observed for real samples. Many researchers have observed that plots of log K, versus log PLo do not yield slopes of -I for PCBs and PAHs, but in fact vary from sample to sample with slopes of the order -0.5 to -1.1 (Baker and Eisenreich 1990, Cotham and Bidleman 1995, Gustafson and Dickhut 1997, McVeety and Hites 1988. Their conclusions were often that the POPs are not at equilibrium.…”
Section: Absorptionmentioning
confidence: 99%